Etika Profesi Guru Di Era Digital : Tantangan Moral Dan Solusi Profesionalisme Dalam Persepektif Pendidikan Islam - Nuril Hidayah; Imron Fauzi (Cendekia Madani Nusantara, 2026)
The digital transformation in the field of education has significantly affected the ethical roles and responsibilities of teachers. This study aims to reveal various forms of ethical crises experienced by teachers in the digital era, their contributing factors, and the strategies needed to strengthen teacher professionalism. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participant observation, and document analysis, including official references from the Ministry of Education and the Indonesian Child Protection Commission (KPAI). The findings indicate that ethical violations do not only occur in the form of verbal or physical misconduct but also in digital forms such as misuse of students’ personal data, plagiarism of teaching materials, and unprofessional interactions on social media. Contributing factors include administrative pressure, low digital ethical literacy, and insufficient regulations governing professional ethics within digital spaces. These findings are discussed in relation to theories of teacher professionalism, educational ethics, and digital literacy. The study highlights the urgency of strengthening digital ethical regulations, providing continuous professional development, and integrating moral values into all aspects of educational technology use. Moreover, it underscores the importance of developing digital ethics grounded in Islamic values such as trustworthiness (amanah), proper conduct (adab), and responsibility as a foundational aspect of teacher professionalism in the digital era. template, namely by looking at the page setup of the template that we have provided. Keywords: Teacher ethics, teacher profesionalism, digital era, ethical violation, islamic ethics